Soil volumetric changes in natric soils caused by air entrapment following seasonal ponding and water table rises - Taboada, Miguel Angel (2001)
Soil volumetric changes have been seldom studied in seasonally ponded soils subjected to periodic water table rises. In the Flooding Pampa of Argentina the topsoils develop significant swelling and shrinkage, despite their low percentages of total and expansible clay. We tested the hypothesis that: (a) the swelling of a Natraquoll and a Natraqualf of this region is caused by the wide change in water contents during ponding-drying cycles; and (b) soil swelling is accentuated by the effect of air entrapment ahead of the advance of soil wetting fronts. The relationship between the reciprocal of bulk density (i.e. soil specific volume), ν, and water content, θ, was determined in the laboratory (clod shrinkage curves) and in the field (repeated core sampling). Soil clods behaved in accordance to their inherent soil properties, with zero and residual shrinkage (slope n = δν/δθ< 1) in both top horizons, and normal shrinkage (slope n = δν/δθ≈ 1) throughout the water content range of Bt horizons. Unlike the clods, in the field the slope, n, was as high as 1.47-1.48 in top horizons, and 1.93-1.98 in both Bt horizons, showing the occurrence of abnormal soil swelling processes. Taking into account the narrow volumetric water content range found in the field (i.e. 0.25 v/v in both Bt horizons), this rejects our first proposed hypothesis. Soil air became trapped ahead of the advance of two field wetting fronts: (a) water table rises from depth and (b) surface ponded water. As a result, pore air volume increased during soil wetting, and was as high as 0.24-0.34 v/v, and 0.35 v/v at the maximum swelling limit of top and Bt horizons, respectively. Results show that air entrapment caused the swelling or "inflation" of soils, which agrees with our second hypothesis. However, the influence of air entrapment was more pronounced than a simple accentuation of swelling in Bt horizons. Air entrapment caused the whole soil to a depth of about 0.4 m to expand.